Enhanced light-matter interaction in gas nitridation-derived TiNx thin films for potential plasmonic applications - Tony, Liya; Selvam, I. Packia; Vinod, C. P.; Potty, S. N. (Journal of Materials Science, 2025)
Titanium nitride is a substitute material exhibiting improved opto-electrical characteristics suitable for plasmonic purposes with adjustable attributes. In this study, we have embraced an innovative methodology for the fabrication of titanium nitride thin coatings via the nitridation of RF magnetron-sputtered titanium metallic films for surface plasmon resonance utilisation. The augmented electrical and optical features of TiN thin coatings prepared through the nitridation procedure are reported for the first time. The metallic coatings underwent gas nitridation at diverse temperatures within the range of 450-600 degrees C. The titanium nitride phase evolution in the coatings was corroborated by x-ray diffraction and x-ray photoelectron spectroscopy examinations. The dielectric function is deduced from reflection spectra through Drude-Lorentz model fitting, and the manifestation of surface plasmon excitation in the visible region was confirmed by correlating with carrier concentration assessments and by ensuring the required negative permittivity in the region. The red shift of screened plasma wavelength was observed with the nitridation temperature, and the same is varied in the wavelength range 400-700 nm. Ultimately, surface plasmons were excited in coatings with optimised thickness using Kretschmann configuration in wavelength interrogation mode.